Dinamika Peradaban dan Pendidikan Pemikiran Islam pada Masa Rasulullah SAW - Wahyu, Wahyu Sihab; Irfan Maulanan Adnan (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This article aims to examine Islamic education during the Prophet's time in the Jahiliyyah era. The basic principles of Islamic education, including revelation-based education, role modeling, integration of religious and worldly knowledge, and the function of the mosque as the center of education, are identified in this study. Using the systematic literature review (SLR) method, this research analyzes many sources, both classical and contemporary, to understand how the education of the Prophet's era had a very strategic role in building Islamic civilization. The results show that the Prophet's education system not only succeeded in forming a generation of companions who excelled in spiritual and intellectual aspects, but also encouraged the birth of a glorious Islamic civilization. The contribution of the Companions after the Prophet Muhammad's death, through strengthening the formal and informal education system, proved that the legacy of Islamic education was sustainable and became the main pillar in the emergence of scientific centers and intellectual dynamics in Islamic history. The legacy of Islamic education is sustainable and becomes the main pillar in the emergence of scientific centers and intellectual dynamics in Islamic history.